What is the Relationship between Islam and Liberalism in the Qur'anic Perspective? (Bagaimana Hubungan Islam dan Liberalisme dalam Perspektif Al-Qur’an) - Dilla Dalailul Hasanah; Diva Nadia Salsabila; Haikal Ali Al Ghifari (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This study examines the relationship between Islam and liberalism, reviews the concept of liberalism, its history, and the perspective of the Qur'an. Liberalism, which emphasizes individual freedom, is often seen as contrary to Islamic principles centered on Sharia. Rooted in the European Renaissance period, liberalism developed in response to the domination of religion and monarchy, encouraging democracy and a free economy. The Qur'an, in verses such as Sura Al-Baqarah, Ar-ra'ad and Al-Isra affirms the importance of obeying the Shari'a and staying away from lust. This research method uses an interpretive approach. Researchers analyze the text and interpretation of the Qur'an to understand the Islamic view of liberalism, with the aim of providing insight into contemporary liberalism discourse.